Compartmentalization of anterogradely and retrogradely transported organelles in axons and growth cones from chick optic tectum - Cheng, TP (J Neurosci, 1988)
Previous work suggests that organelles contacting microtubules in axons are in fast transport. Here, we examine the distribution of organelles contacting microtubules in growing axons and growth cones from chick optic tectum. Five axon segments, each 10 microns long, and 4 entire growth cones were reconstructed from serial electron micrographs of quick-frozen, freeze-substituted chick optic tectum. Organelles contacting microtubules in axons are evenly distributed along all microtubules. Smaller organelles, presumably in anterograde transport, are enclosed in fascicles of microtubules, while larger organelles in retrograde transport lie outside the fascicles. In contrast, organelles contacting microtubules are prevalent only in the most proximal parts of the growth cone, before the microtubule fascicles splay out more distally. The distance between noncontacting organelles and microtubules also becomes progressively greater, reaching a maximum in the mid- and more distal region of the growth cone. Contacts with microtubules of both the smaller, presumably anterogradely transported organelles, as well as the larger, presumably retrogradely transported organelles, abruptly become less frequent in the proximal midregion of the growth cone. It is therefore of possible significance in stopping and starting microtubule-based organelle transport that microtubules change from a straight to an undulating configuration in the midregion of the growth cone. The decrease in organelle binding to microtubules at the demarcations between the straight and undulating microtubule segments may depend on proteins or other local factors as well as the splaying out of the microtubule bundles.